2013
DOI: 10.1258/mi.2012.012034
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Health: Insights, Views & Attitudes (VIVA) survey - Canadian cohort

Abstract: These data indicate that many postmenopausal women in Canada have a low understanding of vaginal atrophy. Medical practitioners should proactively initiate dialogue about this chronic condition with their patients, and discuss appropriate treatment options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 0 publications
0
30
0
4
Order By: Relevance
“…Разнообразие симптомов ГУМС затрудняет точную оценку частоты распространения. По некоторым данным, частота симптомов ГУМС достигает 4 0-5 0 % [8]. В каждом клиническом случае необходимо проводить дифферен циальную диагностику с симптомами вульвовагинальной дермопатии, дисфункцией мышц тазового дна и нейро генной дисфункцией мочевого пузыря.…”
Section: Conflict Of Interest: the Author Declares No Conflict Of Int...unclassified
“…Разнообразие симптомов ГУМС затрудняет точную оценку частоты распространения. По некоторым данным, частота симптомов ГУМС достигает 4 0-5 0 % [8]. В каждом клиническом случае необходимо проводить дифферен циальную диагностику с симптомами вульвовагинальной дермопатии, дисфункцией мышц тазового дна и нейро генной дисфункцией мочевого пузыря.…”
Section: Conflict Of Interest: the Author Declares No Conflict Of Int...unclassified
“…Menopause and aging are important risk factors for urinary symptoms, such as urgency, frequency, nocturia, incontinence, dysuria, and recurrent urinary tract infections [1–3]. These symptoms compromise the quality of life (QOL), sexual function, and social life; they constitute some of the signs and symptoms characterizing genitourinary syndrome of menopause (GSM) [4–8].…”
Section: Introductionmentioning
confidence: 99%
“…A range of surveys have demonstrated that women lack knowledge about the cause, nature, and treatment of postmenopausal vaginal atrophy [10][11][12][13][14] , and 'minimal progress' appears to have been made toward addressing this 10 . Results from the Vaginal Health: Insights, Views & Attitudes (VIVA) survey, originally performed across seven countries in Europe and North America 13,15,16 , suggest that country-specific approaches may be required 13 . The situation in Latin Americawhere women in a gradually aging population may experience a relatively early onset of menopause, with a highly negative impact, and have unequal access to health careis distinctly concerning 17 .…”
Section: Introductionmentioning
confidence: 99%